Perilaku Pencarian Informasi Mahasiswa Program Studi Sarjana Ilmu Perpustakaan Dan Informasi Islam Universitas Muhammadiyah Ponorogo Menggunakan Model Ellis - Ari Suryadi; Jalinur Jalinur (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Introduction. Information-seeking behavior is an essential process that enables students to identify, access, evaluate, and utilize information effectively to support their academic activities. Ellis's information-seeking behavior model provides a comprehensive framework for understanding the stages individuals undertake when searching for information. This study is important because understanding students' information-seeking behavior can provide insights into how they access and use information resources in the digital era. Data Collection Methods. This study employed a descriptive qualitative approach. Data were collected through observation and in-depth interviews with four students from different academic cohorts (2022–2024) in the Islamic Library and Information Science Study Program at Universitas Muhammadiyah Ponorogo. Data Analysis. The collected data were analyzed through the stages of data reduction, data display, conclusion drawing, and verification to obtain a comprehensive understanding of students' information-seeking behavior based on Ellis's model. Results and Discussion. The findings reveal that most participants demonstrated the stages of Ellis's information-seeking behavior model, namely starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending. However, the implementation of these stages varied among participants. Several students did not consistently perform the chaining, differentiating, and monitoring stages, depending on their information needs, search experience, and the availability of information sources. These variations indicate that information-seeking behavior is dynamic and influenced by individual characteristics as well as contextual factors. Conclusion. This study concludes that students generally exhibit systematic information-seeking behavior consistent with Ellis's model, although differences occur in the implementation of certain stages. These findings contribute to a better understanding of students' information-seeking patterns and may serve as a reference for improving information literacy programs and library services in higher education.